Epinephrine Released During Traumatic Events May Strengthen Contextual Fear Memory Through Increased Hippocampus mRNA Expression of Nr4a Transcription Factors - Oliveira, Ana; Martinho, Raquel; Serrão, Paula; Moreira-Rodrigues, Mónica (Frontiers in Molecular Neuroscience, 2018)
Epinephrine (EPI) strengthens contextual fear memories by acting on peripheral β2-adrenoceptors. Phenylethanolamine-N-methyltransferase-knockout mice (Pnmt-KO) are EPI-deficient mice and have reduced contextual fear learning. Our aim was to evaluate the molecular mechanisms by which peripheral EPI strengthens contextual fear memory and if a β2-adrenoceptor antagonist can erase contextual fear memories. Pnmt-KO and wild-type (WT) mice were submitted to fear conditioning procedure after treatment with EPI, norepinephrine (NE), EPI plus ICI 118,551 (selective β2-adrenoceptor antagonist), ICI 118,551 or vehicle (NaCl 0.9%). Catecholamines were separated and quantified by HPLC-ED. Blood glucose was measured by coulometry. Real-time PCR was used to evaluate mRNA expression of Nr4a1, Nr4a2 and Nr4a3 in hippocampus samples. In WT mice, plasma EPI concentration was significantly higher after fear acquisition compared with mice without the test. NE did not increase in plasma after fear acquisition and did not strengthen contextual fear memory, contrary to EPI. Freezing induced by EPI was blocked by ICI 118,551 in Pnmt-KO mice. In WT mice, ICI 118,551 blocked blood glucose release into the bloodstream after fear acquisition and decreased contextual fear memory. Nr4a1, Nr4a2 and Nr4a3 mRNA expression decreased in Pnmt-KO mice compared with WT mice after fear conditioning procedure. In Pnmt-KO mice, EPI induced an increase in mRNA expression of Nr4a2 compared to vehicle. In conclusion, EPI increases in plasma after an aversive experience, possibly improving long-term and old memories, by acting on peripheral β2-adrenoceptors. Glucose could be the mediator of peripheral EPI in the central nervous system, inducing the expression of Nr4a transcription factor genes involved in consolidation of contextual fear memories.